The role of reactive oxygen species in Walker 256 tumour cell and platelet interactions with the vessel wall - Shaughnessy, Gordon Stephen (My University, 1992)
Walker 256 cells (W256 cells) were shown to generate oxygen-derived free radicals when activated with the chemotactic peptide N-formyl-L-Methionyl-L-Leucyl-L-Phenylalanine (fMLP). fMLP-stimulated W256 cells, suspended to a concentration of 5x106 cells/ml, produced luminol chemiluminescence equivalent to that generated by 6.5x10-3 units/ml xanthine oxidase. We also examined human platelets for their ability to generate reactive oxygen species since these are often found at sites of tumour cell arrest in vivo. While others had inferred that human platelets generate reactive oxygen species, we have obtained direct morphological evidence confirming that this can occur. Preliminary studies showed that in the presence of the reactive oxygen species-generating system xanthine-xanthine oxidase, the release of 3H-2-deoxyglucose from prelabeled endothelial cell monolayers was a sensitive index of endothelial cell perturbation. Since the previous experiments suggested that tumour cell contact with the endothelium was required in order to observe isotope release, we asked if the release of 3H-2-deoxyglucose was dependent upon the adhesion of W256 cells to the endothelium. We suggest that W256 cell adhesion to endothelial cell monolayers is partially regulated by vitronectin receptor expression and that endothelial cell perturbation by reactive oxygen species is dependent on tumour cell adhesion. We have also obtained evidence suggesting that W256 cells degrade subendothelial cell matrices by a process involving both the generation of hydrogen peroxide and the secretion of a metalloproteinase. We suggest that the W256 cells can secrete a latent metalloproteinase of molecular weight 94 kD which may be activated, with a loss in molecular weight, by hydrogen peroxide or APMA. In summary, we provide evidence which supports the novel concept that some tumour cells may mediate vessel wall injury by generating reactive oxygen species and suggest that this may promote the metastasis of these cells in vivo. Such a hypothesis has not been postulated previously. (Abstract shortened by UMI.)
Keywords: Molecular Biology; Molecular Biology